SNP2-Lys-C markers inheritance, genes expression, and the resistance of second-generation Catfish Clarias gariepinus against Aeromonas hydrophila infection - Hanggara, Yudha; Alimuddin, Alimuddin; Tri Soelistyowati, Dinar Tri Soelistyowati; Nuryati, Sri (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
High mortality rates in catfish seed caused by motile Aeromonas septicemia disease caused by Aeromonas hydrophila infection. The primary focus is on the genetic selection of the second generation (G2) catfish for resistance to A. hydrophila, utilizing the type-C lysozyme gene at SNP-2 genotype TT. The objective is to assess the inheritance of the SNP2-Lys-C genetic marker from the first generation (G1) Sangkuriang breeders and to evaluate the resistance of the G2 seed to infection. In the experiment, G1 breeders with the TT genotype were spawned, and the resulting G2 seed were challenged with A. hydrophila. The findings indicate that all G2 seed possess the TT genotype and exhibit a higher survival rate compared to the dominant CT genotype seed. The expression of the Lys-C gene in G2 seed is elevated at the onset of infection, decreasing after the seventh day. The expression of the MHC1a and IL-1b genes is also associated with a higher survival rate. The survival of G2 seed correlates with the white blood cell and lysozyme activity, along with an increase in phagocytic activity peaking on the seventh day post-challenge. The conclusion of this study suggests that G2 catfish seed with the TT genotype have stronger resistance to A. hydrophila infection compared to seed with the dominant CT genotype. Keywords: Aeromonas hydrophila, catfish, genotype, lysozyme, resistance ABSTRAK Mortalitas tinggi yang terjadi pada benih lele yang disebabkan oleh penyakit motile aeromonas septicemia akibat Aeromonas hydrophila. Fokus utama adalah pada seleksi genetik generasi kedua (G2) lele untuk resistensi terhadap A. hydrophila, menggunakan gen lisozim tipe-C pada SNP-2 genotipe TT. Studi ini bertujuan menilai pewarisan marka genetik SNP2-Lys-C dari induk sangkuriang generasi pertama (G1) dan mengevaluasi ketahanan benih G2 terhadap infeksi. Dalam eksperimen, induk G1 genotipe TT dipijahkan dan benih G2 yang dihasilkan diuji dengan bakteri A. hydrophila. Hasil menunjukkan bahwa semua benih G2 memiliki genotipe TT dan menunjukkan tingkat kelangsungan hidup yang lebih baik dibandingkan dengan benih dominan genotipe CT. Ekspresi gen Lys-C pada benih G2 tinggi pada awal infeksi, menurun setelah hari ketujuh. Ekspresi gen MHC1a dan IL-1b juga terkait dengan tingkat kelangsungan hidup yang lebih tinggi. Kelangsungan hidup benih G2 berkorelasi dengan jumlah sel darah putih dan aktivitas lisozim, serta peningkatan aktivitas fagositik yang mencapai puncak pada hari ketujuh. Kesimpulan studi ini menunjukkan bahwa benih lele G2 dengan genotipe TT memiliki resistensi yang lebih kuat terhadap infeksi A. hydrophila dibandingkan dengan benih dominan genotipe CT. Kata Kunci: Aeromonas hydrophila, genotipe, ikan lele, lisozim, resistan